Applying user-centered design in the development of nudges for a pragmatic trial to reduce no-shows among veterans. Issue 6 (June 2022) - Zikmund-Fisher, Brian J.; Tuepker, Anaïs; Metcalf, Emily E.; Strange, Wynn; Teo, Alan R.
Highlights: User-centered design (UCD) can be effectively used for refinement of nudge messages. Iterative UCD methods identified nudge messages inappropriate for veterans. Non-judgmental validation may be valuable when communicating with veterans. Abstract: Objective: To incorporate user-centered design processes into the refinement of nudges designed to reduce no-shows among healthcare appointments for military veterans in the Veterans Health Administration (VA). Methods: We developed candidate nudges as brief messages based on four broad concepts in behavioral science. We then conducted iterative waves of multi-stage interviews (N = 27) that included a pile sorting task, a "think-aloud" review of each message, and prototype letter reviews. Rapid consensus analysis of each wave's feedback iteratively refined message language. Results: Veterans rejected several theoretically plausible messages focusing on avoiding the burden of rescheduling missed appointments or the monetary cost of no-shows. Participants suggested framing calling to cancel an appointment as helping other veterans and emphasized a new motivational theme: expressing personal concern for the veteran. Conclusion: Use of iterative UCD methods allowed for early identification of both messages inappropriate for veterans and new veteran-generated nudges around non-judgmental validation that could be incorporated in the design of our pragmatic trial. Practice implications: Rapid team-based qualitative analysis, iterative material design, and space in the study design to incorporate entirely new insights from participants into study materials are all approaches that can improve communications of what matters most to a specific population.